Can we improve emotional skills in older adults? Emotional intelligence, life satisfaction, and resilience - Delhom, Iraida (Colegio Oficial de Psicólogos de Madrid, 2020)
Emotional intelligence has been shown to be a relevant resource associated with better personal and social adaptation. In older adults, it has been associated with constructs such as life satisfaction and resilience, which are of interest in the field of gerontology because of their impact during the aging process. The objective of this study is to test an intervention based on emotional intelligence in order to find out whether the levels of these abilities improve, and whether the inter- vention has an effect on resilience and life satisfaction. The sample was composed of 125 healthy older adults (treatment, n = 57 and control, n = 68). The variables studied were homogeneous between groups. These variables were evaluated using the TMMS-24, SWLS, and BRCS self-report tests. The results showed significant effects of the intervention on the treatment group. Attention levels decreased significantly, whereas clarity and repair increased. In addition, the average scores on resilience and life satisfaction increased. An emotional intelligence-based intervention improves skills of older adults in its three dimensions. In addition, after the intervention, there is an increase in life satisfaction and resilience. Emotional intelligence skills are considered to generate positive, cognitive and behavioral outcomes for adaptation du- ring aging. Thus interventions of this type could contribute to the quality of life of older adults, a topic of great relevance today due to increased longevity.